1993
DOI: 10.1037/0022-3514.64.6.951
|View full text |Cite
|
Sign up to set email alerts
|

Integrating evolutionary and social exchange perspectives on relationships: Effects of gender, self-appraisal, and involvement level on mate selection criteria.

Abstract: Two studies examined which traits males and females desire in partners at various levels of relationship development in an attempt to integrate evolutionary models (which emphasize sex differences) and social exchange models (which emphasize self-appraisals). In Study 1, male and female students specified their minimum criteria on 24 traits for a date, sexual partner, exclusive dating partner, marriage partner, and 1-night sexual liaison. They also rated themselves on the same dimensions. Sex differences were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
353
2
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 419 publications
(394 citation statements)
references
References 36 publications
35
353
2
4
Order By: Relevance
“…Kenrick et al (1990), for instance, found that men rated the personality, friendliness, and sense of humor of a potential marriage partner very highly, and just as highly or more highly than her physical attractiveness (see also Kenrick, Groth, Trost, & Sadalla, 1993). Across cultures, Buss found that men rated the intelligence, kindness, and understanding of a prospective mate as important attributes, and for many men these traits were more important than her physical attractiveness.…”
Section: Personal and Behavioral Attributesmentioning
confidence: 99%
“…Kenrick et al (1990), for instance, found that men rated the personality, friendliness, and sense of humor of a potential marriage partner very highly, and just as highly or more highly than her physical attractiveness (see also Kenrick, Groth, Trost, & Sadalla, 1993). Across cultures, Buss found that men rated the intelligence, kindness, and understanding of a prospective mate as important attributes, and for many men these traits were more important than her physical attractiveness.…”
Section: Personal and Behavioral Attributesmentioning
confidence: 99%
“…The result is that partners are often very similar in terms of age, level of education, ethnic background, religion, and social status (Smits, 1996). Although women are in general slightly younger than their male partner (Buunk et al, 2001;Kenrick et al, 1993). Part of these marriage patterns can be explained by the fact that peoples' choice of partner is constrained by the opportunities available (the supply side argument, see Fisher et al, 1977;Flap, 1999;Huckfeldt, 1983;Marsden, 1990;Kalmijn & Flap, 2001).…”
Section: Positive and Negative Assortative Matingmentioning
confidence: 99%
“…Although evolutionary theorists have agreed about the general principles of sex differences in sexual selection and parental investment, there are a number of alternative hypotheses about how these differences apply to humans (e.g., Buss & Schmitt, 1993;Gangestad & Simpson, 1990Graziano, Jensen-Campbell, Todd, & Finch, 1997;Hazan & Diamond, 2000;Hrdy, 1999;Kenrick et al, 1990;Kenrick, Groth, Trost, & Sadalla, 1993; L. C. Miller & Fishkin, 1997). For example, L. C. Miller and Fishkin (1997) argued that both sexes are primarily inclined toward monogamy, whereas Hrdy (1999) has advanced arguments that primate females in general, and human females in particular, are more promiscuous than is generally thought.…”
Section: Sex Differences and The Dynamics Of Matingmentioning
confidence: 99%